Pengaruh Penggunaan Media Pembelajaran Interaktif Terhadap Hasil Belajar Pada Mata Pelajaran Ilmu Pengetahuan Alam (IPA) Siswa Kelas IV SDN Cupak - Exela Nurfadilah; Meldi Ade Kurnia Yusri (Journal of Pedagogy and Online Learning, 2022)
Schools have a significant position in the smooth process of education. At this time, education providers are increasingly aware of the meaning of media that supports education. Learning by using interactive media can be used as an alternative source to reduce student saturation in the educational process. especially can be used when science education at the SDN Cupak level. Therefore, the case studied in this study is "Is there any effect of using interactive media based on Adobe Flash CS6 on fourth grade students at SDN 12 and SDN 05 Cupak, Solok Regency." It consists of 2 classes, namely the experimental class and the control class. With the method of equating the experimental class, namely class IV SDN 12 Cupak with treatment using interactive educational media and the control class, class IV SDN 05 Cupak being treated not using interactive media. Having the same number of students is 25 people. This research was conducted on science subjects in semester 2 of the 2021/2022 academic year. For hypothesis testing, this study used t-test statistics, with a significant level of 5% (= 0.05). The results showed that the average value of the experimental class using interactive media was 80.36. The average value of the control class that does not use interactive media is 70.84. Based on the calculation of the t-test (t-test) obtained tcount 7.43 otherwise ttable at a significant level 0.05 = 2.01. When compared, so that tcount > ttable is 7.43 > 2.01. Which means that H0 is rejected as well as H1 is accepted. Thus the use of interactive media significantly affects the science learning outcomes of fourth grade students at SDN 12 Cupak.